Scaling Up Nutrition : What Will it Cost? - Horton, Susan (Washington, DC: World Bank, 2012)
Undernutrition imposes a staggering cost worldwide, both in human and economic terms. It is responsible for the deaths of more than 3.5 million children each year (more than one-third of all deaths among children under five) and the loss of billions of dollars in forgone productivity and avoidable health care spending. Individuals lose more than 10 percent of lifetime earnings, and many countries lose at least 2-3 percent of their gross domestic product to undernutrition. The current economic crisis and its potential impact on the poor make investing in child nutrition more urgent than ever to protect and strengthen human capital in the most vulnerable developing countries. This report offers suggestions on how to raise these resources. It is an investment we must make. It will yield high returns in the form of thriving children, healthier families, and more productive workers. This investment is essential to make progress on the nutrition and child mortality Millennium Development Goals (MDGs) and to protect critical human capital in developing economies. The human and financial costs of further neglect will be high. This call for greater investment in nutrition comes at a time when global efforts to strengthen health systems provide a unique opportunity to scale up integrated packages of health and nutrition interventions, with common delivery platforms, and lower costs. The report has benefited from the expertise of many international agencies, nongovernmental organizations, and research institutions. The cooperation of so many practitioners is evidence of a growing recognition of the need to invest in nutrition interventions, and a growing consensus about how to deliver effective programs.